Household Perception and Evaluation on Tree Planting Activities for Landscaping at Taman Rashibah Indah, Seremban Negeri Sembilan - Aziz, Wilter @ Azwal (2000)
The relationship of man to the environment particularly trees need no further elaboration. Human altitudes and awareness toward tree planting is always changing over times. A study was carried out to evaluate the perception, preferences and awareness of people staying in Taman Rashibah Indah, Seremban toward tree planting activities in their residential area. A Survey was carried out by using a questionnaire to 251 respondents that represent every houses in this area. Data obtained were analyzed using SPSS Computer Program and respondent evaluation and perception were determined using average and percentage value. The influences of background to the respondent perception was also tested by using T test and Analysis of Variance (ANOVA) at 95 percent confident level. The majority of the residents in this area are Malay aged from 26 to 45 years old. About 90 percent of residents owned their houses. Overall the result indicated that respondents were not satisfied with the tree condition in this residential area. Majority of them agreed that trees are beneficial in to their residential area especially for filtering the pollution and creating more attractive surrounding. Moderate in size, shape and growth rates are preferred by the residents, but they prefer trees of diverse species. Most of the residents felt that tree planting and maintenance activities are the responsibility of the local authority. Fruit trees are one of the suggested trees to be planted. The background of the respondent has no effect on respondent's perception in the planting activities. The number of tree needs to be increase in this area.